The Complexity Analysis in Dual-Channel Supply Chain Based on Fairness Concern and Different Business Objectives. (20th May 2018) - Qiu-xiang, Li; Yu-hao, Zhang; Yi-min, Huang
Abstract : We study a dual-channel supply chain which consists of one dual-channel manufacturer and one traditional retailer considering fairness concern. The manufacturer takes the market share as one of its business objectives in the competition game. We are devoted to establishing a vertical Nash game model and analyzing the price evolution of the model via the method of complexity theory and take adaptive adjustment control method to control the system's chaotic state. The results show that an excessive price adjustment speed will hurt the system's stability as well as profit of the supply chain. A high level fair caring for retailer will push the system to fall into chaos earlier, while a higher level fair caring for manufacturer will enlarge the stability region of the system. Setting the different objectives by the manufacturer will cause drastic competition in dual-channel supply chain. The research of this paper is of great significance to the decision-makers' price decision and supply chain operation management.